Multi-Stakeholder Perspectives on Scaling up UK Fashion Upcycling Businesses. (1st September 2020) - Sung, Kyungeun; Cooper, Tim; Oehlmann, Johanna; Singh, Jagdeep; Mont, Oksana
Abstract: Fashion upcycling, the process of using waste clothing and textiles to create new products, is an alternative to business-as-usual practices which can effectively address concerns on excessive consumption of energy and material resources and use of chemicals in the fashion industry. Scaling up fashion upcycling businesses could enable the transition of the fashion industry towards sustainability. Past studies in fashion upcycling have paid attention to limited aspects of the businesses, and comprehensive synthesis of viewpoints from diverse stakeholders involved in the business is lacking. This paper provides such a synthesis, focusing on the challenges and success factors for expanding (or scaling up) UK fashion upcycling businesses. Twenty three stakeholders in the UK were interviewed. Four different perspectives (by material suppliers, upcyclers, retailers and consumers) on challenges and success factors for scaling up fashion upcycling businesses in the UK as well as suitable actors to take actions for positive change were identified. Common challenges and success factors across stakeholders were highlighted. The paper further discusses theoretical and practical implications of the study.